SILVIELLA, NUEVO GENERO DE PHYLLOBAENINAE (COLEOPTERA, CLERIDAE) DE LA PARTE MERIDIONAL DE AMERICA DEL SUR - Solervicens, Jaime (Acta Entomológica Chilena, 2022)
A new genus is created to receive lwo species segregated from Eurymetopum Blanchard, 1844 and a new one. A study of the type material of all the laxa included was made. Species are characterized on the basis of exlernal morphology, coloration and the structure of the male and female genitalia, using seríes of material representing their entire distributional ranges. Descriptions are accompanied by figures of the species and their characters of taxonomical valué. A key is provided and geographical distributions are maped.